PENGEMBANGAN SISTEM INFORMASI KLINIK PADA KLINIK BENGAWAN MEDISTRA - , PRAMUDYA WARDHANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Along with the development of technology and high competitiveness in the clinic, information systems is needed to manage a clinical activity, which plays a role in terms of service and presentation of data to be more fast, precise, and accurate. In an effort to improve business clinics, which typically encountered obstacles that clinics should improve their services with the ability to manage all clinical data and presenting information more quickly, precisely, and accurately. The problem is a lack of clinical information systems that can be used in real time to serve patients and data processing of the patient data from registration to payment process. So, it takes the making of web-based clinical information systems to improve the effectiveness of patient enrollment process until the payment. This information system is built using a web-based PHP programming language supported by the framework CodeIgniter, Javascript with JQuery framework, Apache web server, and MySQL for the database management system. This system has several integrated modules, such as the admin module, patient data management module, nursing data management module, examination data management module, pharmacy data management module, transaction data management module.